Child-Protection Systems – Czech Perspective - Kornel, Martin (Child-Protection Systems, 2025)
Abstract:The Czech Republic’s child protection system, assessed as risk-oriented with high intervention thresholds, faces many challenges such as fragmentation, excessive institutionalisation of children care and inadequate participation of children and parents, despite recent strategic aims for reform. However, its guiding principles encompass the best interest of the child, family protection, respect for children’s participation rights, non-discrimination, prevention, cultural sensitivity, rehabilitation and voluntary participation. The responsibility for maintaining the Czech child protection system is divided among various actors, mainly socio-legal protection bodies, courts and social service providers. The system pays special attention to children at risk, including those lacking care, exhibiting problematic behaviour, being crime victims or having been frequently institutionalised. The system provides some specific measures for children with disabilities, but some accessibility issues, as a heritage of the past, persist. The state’s intervention in the family for children’s protection relies strongly on the activities of socio-legal protection bodies, which are mainly preventive, advisory, educational, and protection measures. The system provides various benefits regarding social support, pension and tax law systems. Moreover, a variety of paid and unpaid child welfare is provided, mainly social activation services, low threshold facilities for children and minors, respite care, accompanying organisations services for foster parents and adoptive parents and residential care centres. When considering alternative care arrangements for children, courts have a wide array of options under the law, including placing the child under the care of a guardian, another person (typically a relative) or foster care, with various provisions for short-term and long-term arrangements. Additionally, institutional care is an alternative to be employed only if other substitute family care is impossible. Keywords: child protection system, institutional care, social-legal protection of children, foster care, social services